ANALISIS YURIDIS PENETAPAN PERKARA NOMOR 199/PDT.P/PA PADANG TENTANG ASAL USUL ANAK YANG TIDAK MEMILIKI AKTA KELAHIRAN DI PENGADILAN AGAMA KELAS IA PADANG - Karsa Setiaman Zalukhu, Abd. Rahmad dan (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Children are the next generation of the nation that we must always look after because they have inherent dignity and rights as human beings that must be upheld. Article 55 paragraph (1) of Law Number 1 of 1974 concerning marriage explains that the origin of a child can only be proven by an authentic birth certificate issued by an authorized official. . The formulation of the problem is: What is the judge's consideration in Case Number 199/Pdt.P/2022/PA.Pdg concerning Determining the Origin of Children who do not have a Birth Certificate in the Padang Class 1A Religious Court and what is the juridical analysis of the Decision in Case Number 199/Pdt.P/2022 /PA.Pdg Regarding Determining the Origin of Children Who Do Not Have Birth Certificates at the Padang Class 1A Religious Court. The approach to the problem in this research is Normative Juridical, a technique for collecting library study data and then processing it through editing and coding processes, and analyzed qualitatively. Based on the research results, it can be concluded that: The judge's consideration regarding determining the origin of children who do not have birth certificates is that the applicant and respondent need a determination from the Religious Court to serve as a legal basis for processing and obtaining the child's birth certificate. and the respondent had an unregistered marriage before the applicant's child was born and the applicant and respondent were willing to marry officially and be registered at the KUA, with sufficient evidence and witnesses, the panel of judges granted the decision as the legal basis for the Padang City population and civil registration service to issue the birth certificate of children of the applicant and respondent. Juridical analysis regarding the determination of the origins of children who do not have a birth certificate, applicant I and applicant II have gone to process the child's birth certificate at the Padang City civil registration office, but the officer at the civil registration office is not authorized to issue the child's birth certificate because there is no determination from the Court. Padang Religion. So the applicant and respondent first officially married at the KUA office. Article 103 paragraph 1 of Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law explains that the origin of a child can only be proven by a birth certificate or other evidence.